2017
DOI: 10.3390/met7100432
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Crack Propagation in Nanoscale Polycrystal Nickel Based on Different Strain Rates

Abstract: Based on the strain rates of 2 × 10 8 s −1 and 2 × 10 10 s −1 , molecular dynamics simulation was conducted so as to study mechanisms of crack propagation in nanoscale polycrystal nickel. The strain rate has an important effect on the mechanism of crack propagation in nanoscale polycrystal nickel. In the case of a higher strain rate, local non-3D-crystalline atoms are induced and Lomer-Cottrell locks are formed, which plays a critical role in crack initiation and propagation. Orientation difference between adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Molecular dynamics simulations are widely used for these applications and allow easy modelling and accurate calculations that are easy to intuitively carry out. [15][16][17][18] This study uses molecular dynamics simulations. The embedded atom method (EAM) is used to simulate the microstructure evolution of Nibased single-crystal alloys.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular dynamics simulations are widely used for these applications and allow easy modelling and accurate calculations that are easy to intuitively carry out. [15][16][17][18] This study uses molecular dynamics simulations. The embedded atom method (EAM) is used to simulate the microstructure evolution of Nibased single-crystal alloys.…”
Section: Methodsmentioning
confidence: 99%
“…Eventually, they develop an approximative scheme to estimate grain-boundary energies for varying C and H contents, and they consider the dependence of hydride formation on the grain-boundary stiffness. When it comes to time evolution and dynamical phenomena, the paper by Zhang and Jiang [6] deals with molecular-dynamics simulations of crack propagation in nanoscale polycrystalline nickel. The strain rate has an important effect on the mechanism of crack propagation, and for higher strain rates local, non-3D-crystalline atoms show up, and Lomer-Cottrell locks are formed.…”
Section: Contentmentioning
confidence: 99%
“…Yang et al [18] revealed that the fatigue cracks in the Ni-Fe alloy caused by the coalescence of nanovoids are before the main crack tips. For polycrystal, Zhang et al [19] studied the strain rate effect on the crack propagation mechanisms of nickel. Zhou et al [20] extracted the da/dN metrics from the fatigue crack growth in polycrystal coherent twins.…”
Section: Introductionmentioning
confidence: 99%